Multi-Step Combined Control Technology for Karst and Fissure Water Inrush Disaster During Shield Tunneling in Spring Areas - Huang, Xing; Li, Linfeng; Zhang, Chaofan; Liu, Bin; Li, Kejin; Shi, Hongbing; Jing, Boyu (Frontiers in Earth Science, 2021)
Shield tunneling in highly fractured karst water-rich conditions easily results in water inrush disaster or even causes the roof of the karst caves to collapse. Severe water inrush disasters have occurred during the EPB (earth pressure balance) shield machine of the Jinan Metro Line R1 advanced through a karst and fissure groundwater-rich limestone ground in the spring area. To cope with the extreme water inrush risk, a multi-step combined control technology was put forward. First, a detailed geological exploration was carried out by ahead geophysical prospecting using high-density resistivity method, geological radar, etc., and geological borehole drilling was conducted from the ground surface before excavation. As a result, the distribution orientation, size, fissure development degree, and water inflow channel within the surrounding rock of the karst caves were detected. Second, multi-step grouting was performed to reinforce the surrounding rock, including pre-grouting treatment and filling rock blocks to the big karst caves from the ground surface, multiple grouting with a small amount of inert slurry each time inside the tunnel, and secondary circumferential hoop grouting at the shield tail. Third, the tunneling process was optimized, including optimizing the tunneling parameters, making full use of the air-pressurized tunneling technology of the EPB to press bentonite into the fractures around the excavation cabin to seal the fissure water, and using the drainage system of EPB and muck improvement technology to reduce the water inrush disaster. Meanwhile, shield protection slurry technology is applied to cutter inspection and replacement in the pressurized chamber under dynamic water flow environment of the spring terrain. The practice shows that the water inrush on the tunnel face is obviously alleviated after the shield machine advanced into the grouting area. According to statistics, the water inflow on the tunnel face decreases from about 4 m3/h before treatment to less than 0.3 m3/h after the abovementioned control, and the water seepage between the segmental linings reduces to almost zero. The average advance rate increased from 3 m/day without stopping or even zero when the shield machine needs to shut down 2–3 days for drainage to about 6 m/day. In addition, the treatments prevented the shield machine from jamming and the head descending disaster. This study provided a reliable control method for shield tunneling through the karst and fissure water-rich area and played an essential role in protecting the spring water.